Faktor-Faktor yang Memengaruhi Minat Masyarakat Muslim Jabodetabek Terhadap Bank Digital Syariah - Astika Putri, Citra Kirana; Tati Handayani (Universitas Islam Negeri Alauddin Makassar, 2025)
Sharia digital banks are developing as an alternative financial service that is easier and more efficient. However, the existence of Sharia digital banks hasn’t yet competed with conventional digital banks. Services from various bank brands are also a consideration to use them. This study aims to analyze factors such as Islamic branding, service features, digital literacy, and digital marketing in influencing the interest of the Jabodetabek Muslim community in Sharia digital banks. The sample of this research was 100 respondent Muslim from Jabodetabek. The research method uses quantitative descriptive. Data collected by distributing questionnaires. Data analysis used the PLS method. The results indicate that Islamic branding and digital marketing influence the interest of the Jabodetabek Muslim community in Sharia digital banks, while service features and digital literacy have no effect. The implication of this research is that Sharia digital banks need to strengthen their brand image as Islamic banks by providing service features that are able to demonstrate their superiority compared to other types of banks, as well as reaching the public in a more attractive way